Fibrinogen supplementation for the trauma patient: Should you choose fibrinogen concentrate over cryoprecipitate?. Issue 4 (15th October 2022) - Obaid, Omar; Anand, Tanya; Nelson, Adam; Reina, Raul; Ditillo, Michael; Stewart, Collin; Douglas, Molly; Friese, Randall; Gries, Lynn; Joseph, Bellal
Abstract : Fibrinogen supplementation for bleeding trauma patients using fibrinogen concentrate instead of cryoprecipitate is associated with earlier fibrinogen administration and improved outcomes. Abstract : BACKGROUND: Trauma-induced coagulopathy is frequently associated with hypofibrinogenemia. Cryoprecipitate (Cryo), and fibrinogen concentrate (FC) are both potential means of fibrinogen supplementation. The aim of this study was to compare the outcomes of traumatic hemorrhagic patients who received fibrinogen supplementation using FC versus Cryo. METHODS: We performed a 2-year (2016–2017) retrospective cohort analysis of the American College of Surgeons Trauma Quality Improvement Program database. All adult trauma patients (≥18 years) who received FC or Cryo as an adjunct to resuscitation were included. Patients with bleeding disorders, chronic liver disease, and those on preinjury anticoagulants were excluded. Patients were stratified into those who received FC, and those who received Cryo. Propensity score matching (1:2) was performed. Outcome measures were transfusion requirements, major complications, hospital, and intensive care unit lengths of stay, and mortality. RESULTS: A matched cohort of 255 patients who received fibrinogen supplementation (85 in FC, 170 in Cryo) was analyzed. Overall, the mean age was 41 ± 19 years, 74% were male, 74% were white and median Injury Severity Score was 26 (22–30). Compared with the Cryo group, the FC group required less units of packed red blood cells, fresh frozen plasma, and platelets, and had shorter in-hospital and intensive care unit length of stay. There were no significant differences between the two groups in terms of major in-hospital complications and mortality. CONCLUSION: Fibrinogen supplementation in the form of FC for the traumatic hemorrhagic patient is associated with improved outcomes and reduced transfusion requirements as compared with Cryo. Further studies are required to evaluate the optimal method of fibrinogen supplementation in the resuscitation of trauma patients. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :